Complementation of intramolecular interactions for structural–functional stability of plant serine proteinase inhibitors - Joshi, Rakesh S.; Mishra, Manasi; Suresh, C.G.; Gupta, Vidya S.; Giri, Ashok P. (Biochimica et biophysica acta, 2013)
Plant protease inhibitors (PIs) constitute a diverse group of proteins capable of inhibiting proteases. Among PIs, serine PIs (SPIs) display stability and conformational restrictions of the reactive site loop by virtue of their compact size, and by the presence of disulfide bonds, hydrogen bonds, and other weak interactions. The significance of various intramolecular interactions contributing to protein folding mechanism and their role in overall stability and activity of SPIs is discussed here. Furthermore, we have reviewed the effect of variation or manipulation of these interactions on the activity/stability of SPIs. The selective gain or loss of disulfide bond(s) in SPIs can be associated with their functional differentiation, which is likely to be compensated by non-covalent interactions (hydrogen bonding or electrostatic interactions). Thus, these intramolecular interactions are collectively responsible for the functional activity of SPIs, through the maintenance of scaffold framework, conformational rigidity and shape complementarities of reactive site loop. Structural insight of these interactions will provide an in-depth understanding of kinetic and thermodynamic parameters involved in the folding and stability mechanisms of SPIs. These features can be explored for engineering canonical SPIs for optimizing their overall stability and functionality for various applications. [Display omitted] •Disulfide bond network and alliance of weak interactions provides stability to SPIs.•Selective loss of a disulfide bond is associated with functional differentiation in SPIs.•Interplay of intramolecular interactions might have evolutionary significance.